2006
DOI: 10.1590/s0103-64402006000200015
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the tongue after bone marrow transplantation in a patient with Fanconi anemia

Abstract: Fanconi anemia (FA) is an autosomal recessive disorder that might cause a variety of congenital and developmental abnormalities. The most important features of FA are progressive bone marrow failure and development of malignancies, particularly acute myeloid leukemia and solid tumors. This paper reports the case of a 12-year-old patient with FA assisted at the Stomatology and Bucomaxillofacial Cancer Prevention Service of São Lucas Hospital, Brazil, who had been submitted to bone marrow transplantation (BMT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
(24 reference statements)
0
20
0
1
Order By: Relevance
“…The main cause of morbidity and mortality are aplastic anemia, myelodysplasia and Although acute myeloid leukemia is the most commonly found malignancy, solid tumors represent about 40% of neoplasms observed which develop at older ages in patients surviving the hematologic abnormalities [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main cause of morbidity and mortality are aplastic anemia, myelodysplasia and Although acute myeloid leukemia is the most commonly found malignancy, solid tumors represent about 40% of neoplasms observed which develop at older ages in patients surviving the hematologic abnormalities [5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in contrast to FA-nonaffected individuals, predisposing risk factors for head and neck cancer, like tobacco and alcohol abuse, are rare in these patients. Jansisyanont reported that the commonest localizations of SCC in FA patients in descending order are: tounge, anogenital region, pharynx, larynx, oral [5] mucosa, mandible and skin [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the lesions and conditions with potential to become malignant, such as leukoplasias, erythroplasias, lichen planus, and squamous cell carcinoma itself must be considered important alterations in the tongue in individuals with FA, particularly post-BMTO, because this is the site of preference for these alterations, with a prevalence of 69% 19 . The alveolar ridge, retromolar trigone region, floor of the mouth, oral mucosa and gingivae are the areas of the major establishment of squamous cell carcinoma [20][21][22][23][24][25] . Squamous cell carcinoma occurs with greater frequency in the region of the head and neck, particularly after bone marrow transplantation [17][18] , with the tongue being the site of preference.…”
Section: Tongue Lesionsmentioning
confidence: 99%
“…In general, the age for the development of neoplasias in patients with FA is significantly lower than the age at which these same alterations manifest themselves in the population in general 14. In the head and neck region, the mean age for the appearance of tumors in the general population is around 45 years, while in individuals with FA, the age is 32 years 19 . Reports of SCC in children [18][19][20][21][22][23][24] , adolescents 16,[26][27] , and young adult [17][18][19][20][21][22][23][24][25][26][27][28] , individuals with FA suggest genetic alterations in these individuals as the etiological factor of SCC of the tongue.…”
Section: Tongue Lesionsmentioning
confidence: 99%